Ablation Measurements at Schiaparelli Glacier, Cordillera Darwin, Chile, with an automatic ablation sensor, 2016-2017 - Netto, Guilherme; Arigony-Neto, Jorge; Jaña, Ricardo; Gonzalez, Inti; Schneider, Christoph; Temme, Franziska (PANGAEA, 2023)
The data set contains measurements of surface ablation recorded by an automatic ablation sensor at the frontal part of Schiaparelli Glacier, Cordillera Darwin, Chile. The sensor was installed by the Universidade Federal do Rio Grande, Brazil, in September 2016 and uninstalled in November 2017. The sensor records the time passed for every 15 cm of surface lowering. Unrealistic records have been excluded. The data set gives the name, latitude (latitude), longitude (longitude), start of the period (Date1), end of the period (Date2) and total ablation during that period (ablation).